2016
DOI: 10.1021/acsami.6b07068
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated Degradation Behavior and Cytocompatibility of Pure Iron Treated with Sandblasting

Abstract: Fe-base materials are of interest to be used in biodegradable implants. However, their corrosion rate in the biological environment may be too slow for the targeted applications. In this work, sandblasting is applied as a successful surface treatment for increasing the degradation rate of pure iron in simulated body fluid. Two sandblasting surfaces with different roughness present various surface morphologies but similar degradation products.Electrochemistry tests revealed that sandblasted samples have a highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 43 publications
0
43
0
Order By: Relevance
“…The prepared thin films decreased the degradation rate and enhanced the corrosion behavior [166]. Sandblasting method has been proposed by Zhou et al [167] as a successful surface treatment for increasing the degradation rate of pure Fe in SBF. The reasons for increasing the corrosion rate were the change of surface composition (in the early stage), high roughness and high density of dislocations [167].…”
Section: Ironmentioning
confidence: 99%
See 1 more Smart Citation
“…The prepared thin films decreased the degradation rate and enhanced the corrosion behavior [166]. Sandblasting method has been proposed by Zhou et al [167] as a successful surface treatment for increasing the degradation rate of pure Fe in SBF. The reasons for increasing the corrosion rate were the change of surface composition (in the early stage), high roughness and high density of dislocations [167].…”
Section: Ironmentioning
confidence: 99%
“…Sandblasting method has been proposed by Zhou et al [167] as a successful surface treatment for increasing the degradation rate of pure Fe in SBF. The reasons for increasing the corrosion rate were the change of surface composition (in the early stage), high roughness and high density of dislocations [167]. The limited number of researches in the surface treatment methods for Fe-based BM wires indicates that more studies is required to introduce and reveal the potentials of various surface treatments approaches.…”
Section: Ironmentioning
confidence: 99%
“…Zhou et al . prepared silicon carbide (SiC) thin films on the Fe surface through sandblasting treatment[ 12 ]. They found that surface morphology, surface composition, and surface area of Fe were changed, causing higher weight loss.…”
Section: Introductionmentioning
confidence: 99%
“…Just recently, surface-roughness modifications, like sandblasting and laser texturing, have been shown to greatly modify the corrosion properties. [30][31][32][33][34][35] For example, the corrosion is significantly accelerated if the surface wettability after laser texturing is increased [35]. In this case, the interaction between a laser pulse and metal surface modify both, surface topography and its chemistry, since usually metal oxides are formed.…”
Section: Introductionmentioning
confidence: 99%